Community-Based Tourism as a solution to Reduce the Negative Impact of Mass Tourism - Nainggolan, Hetty Claudia; Prihadi, Donny Juliandri; Mulyana, Hadi (PT. Hafasy Dwi Nawasena, 2024)
Community-based tourism (CBT) has become an alternative approach that aims to address the negative impacts of mass tourism on the environment, culture, and local economy. This concept places local communities as the main actors in the management of tourist destinations, which not only strengthens their role in decision-making but also provides direct economic benefits. Thus, CBT has great potential to improve people's welfare while minimizing ecosystem damage and degradation of cultural values. This study uses the Systematic Literature Review (SLR) method to evaluate the successful implementation of CBT in various global destinations and examine the challenges faced by local communities in maintaining the sustainability of this model. This article analyzes more than 50 related literature to explore how CBT can be effectively applied as a long-term solution. Based on the results of the study, it was found that the CBT approach is able to balance tourism growth with environmental conservation and cultural preservation. However, challenges such as limited community capacity, lack of government support, and the threat of commercialization must be addressed through inclusive and collaborative policies. This article concludes with strategic recommendations for the development of sustainable community-based tourism.